(untitled) (Studia Prawnicze / The Legal Studies, 2002)
Autor artykułu przybliża czytelnikom idee państwa prawnego w Polsce oraz wpływ kultury prawnej na nią. Zostają omówione podstawowe założenia ustrojowe Rzeczypospolitej Polskiej takie jak zasada państwa prawnego, która zawiera w sobie standardy takie jak m. in. demokratyczne formy legitymizacji władzy, zasadę konstytucjonalizmu, podział władzy, niezawisłe sądownictwo, sądownictwo administracyjne czy gwarancje praw i wolności obywatelskich. Ponadto autor przedstawia swoje refleksje nad współczesnym społeczeństwem polskim w kontekście niedostatku kultury prawnej i politycznej u rządzących. The author of the article introduces readers to the idea of the rule of law in Poland and the influence of legal culture on it. The basic constitutional assumptions of the Republic of Poland are discussed, such as the rule of law, which includes standards such as democratic forms of legitimacy of power, the principle of constitutionalism, the separation of powers, the independent judiciary, administrative judiciary or guarantees of civil rights and freedoms. In addition, the author presents his reflections on the contemporary Polish society in the context of the paucity of legal and political culture of people in power.